The Contribution of Polysaccharide Antigens From Clinical Proteus spp. and Klebsiella spp. Isolates to the Serological Cross-Reactions - Palusiak, Agata (Frontiers in Cellular and Infection Microbiology, 2021)
Klebsiella spp. and Proteus spp. cause hospital acquired urinary tract infections (UTIs), which are often related to the use of catheters. To create a vaccine preventing from UTI, immunogenic bacterial antigens with common epitopes are still being looked for. In this work the role of polysaccharide antigens of four Klebsiella spp. and eight Proteus spp. strains in serological cross reactions with specific antisera was examined. An enzyme-linked immunosorbent assay (ELISA), Western blot technique and silver staining by Tsai method were performed. The Klebsiella and Proteus spp. LPSs and cells were used as antigens. The polyclonal rabbit sera specific to Klebsiella oxytoca 0.023 and 0.062 strains and four Klebsiella spp. LPSs were obtained. The ELISA and Western blot results showed the strongest cross reactions occurring between lipopolysaccharides (LPSs) from four Klebsiella strains and P. vulgaris O42 antiserum. The silver-staining procedure revealed the patterns typical of both slow- and fast-migrating mass species of the Klebsiella LPSs. The Klebsiella spp. antigens also cross reacted with four P. penneri antisera and most of the reactions were observed as low-migrating patterns. The 0.023 antiserum weakly cross reacted with high molecular-mass species containing LPS with O-polysaccharides of P. penneri 60 LPS whereas for the K. oxytoca 0.062 antiserum such reactions were observed for P. penneri 19, 22 and 60 LPSs. Obtaining cross reactions between the antigens of Klebsiella strains and Proteus antisera is important for proving the immunogenic role of polysaccharide antigens in triggering the immunological response.